Ciri kanak-kanak berpenglihatan terhad di Klinik Penglihatan Terhad UKM - Rokiah Omar,; Victor Feizal Knight,; Zainora Mohammed,; Tholasee G.M, (penerbit ukm, 2007)
While the prevalence of visually impaired children constitutes a small portion of the visually impaired population, it is important to determine whether the Jurnal Sains Kesihatan Malaysia 5 (1) 2007: 37-45 38 low vision services available are utilised by these children. This is important as previous studies have shown that children have a very high rate of successful low vision device use compared to adults. This was a cross sectional retrospective study. Fifty nine low vision clinic children records were evaluated. The results showed that 25.4% of the children were categorised as with moderate low vision, 30.5% with severe low vision and 40.7% were categorised as blind. The major causes of low vision were congenital cataract, congenital nystagmus, congenital glaucoma, macular degeneration and retinitis pigmentosa. Low vision rehabilitation for near work using magnifiers improved the vision of 30.5% of the low vision children. This finding suggests that 1/3 of low vision children could benefit from low vision rehabilitation. The low vision devices most commonly prescribed to the children in this study were stand magnifiers, hand-held magnifiers and spectacles. This study illustrates the key role of optometrists in the management of visual impairment in Malaysian children. It would appear that the establishment of low vision services in government hospitals using trained optometrists is a cost effective method of service delivery. Therefore more low vision children would have access to proper low vision rehabilitation and through that rehabilitation, their quality of life can be improved.